Pim1 Kinase Overexpression Enhances Ckit(+) Cardiac Stem Cell Cardiac Repair Following Myocardial Infarction in Swine - Kulandavelu, Shathiyah (J Am Coll Cardiol, 2016)
BACKGROUND: Pim1 kinase plays an important role in cell division, survival, and commitment of precursor cells towards a myocardial lineage, and overexpression of Pim1 in ckit(+) cardiac stem cell (CSC) enhances their cardioreparative properties. OBJECTIVES: We sought to validate the effect of Pim1-modified CSCs in a translationally relevant large animal preclinical model of myocardial infarction (MI). METHODS: Human CSCs (hCSCs, n = 10), hckit(+) CSCs overexpressing Pim1 (Pim1(+); n = 9), or placebo (n = 10) were delivered by intramyocardial injection to immunosuppressed Yorkshire swine (n = 29) 2 weeks after MI. Cardiac magnetic resonance and pressure volume loops were obtained before and after cell administration. RESULTS: Whereas both hCSCs reduced MI size compared to placebo, Pim1(+) cells produced a ~3-fold greater decrease in scar mass at 8 weeks post-injection compared to hCSCs (−29.2 ± 2.7% vs. −8.4 ± 0.7%; p < 0.003). Pim1(+) hCSCs also produced a 2-fold increase of viable mass compared to hCSCs at 8 weeks (113.7 ± 7.2% vs. 65.6 ± 6.8%; p < 0.003), and a greater increase in regional contractility in both infarct and border zones (both p < 0.05). Both CSC types significantly increased ejection fraction at 4 weeks but this was only sustained in the Pim1(+) group at 8 weeks compared to placebo. Both hCSC and Pim1+ hCSC treatment reduced afterload (p=0.02 and p=0.004, respectively). Mechanoenergetic recoupling was significantly greater in the Pim1+ hCSC group (p = 0.005). CONCLUSIONS: Pim1 overexpression enhanced the effect of intramyocardial delivery of CSCs to infarcted porcine hearts. These findings provide a rationale for genetic modification of stem cells and consequent translation to clinical trials.